Anticoagulation therapy patterns for acute treatment of venous thromboembolism in GARFIELD‐VTE patients. (23rd July 2019) - Haas, Sylvia; Ageno, Walter; Weitz, Jeffrey I.; Goldhaber, Samuel Z.; Turpie, Alexander G. G.; Goto, Shinya; Angchaisuksiri, Pantep; Dalsgaard Nielsen, Joern; Kayani, Gloria; Zaghdoun, Audrey; Farjat, Alfredo E.; Schellong, Sebastian; et al.
Abstract: Background: Parenteral anticoagulants and vitamin K antagonists (VKAs) have constituted the cornerstone of venous thromboembolism (VTE) treatment. Meanwhile, direct oral anticoagulants (DOACs) provide physicians with an alternative. The Global Anticoagulant Registry in the FIELD (GARFIELD)‐VTE observes real‐world treatment practices. Objectives: Describe initial anticoagulation (AC) treatment patterns in VTE patients who received parenteral AC, VKAs, and/or DOACs within ±30 days of diagnosis. Methods: VTE patients were categorized into parenteral AC only, parenteral AC with transition to VKA, VKA only, parenteral AC with transition to DOAC, and DOAC only. Results: A total of 9647 patients were initiated on AC treatment alone. 4781 (49.6%) patients received DOACs ± parenteral ACs; 3187 (33.0%), VKA ± parenteral ACs; and 1679 (17.4%) parenteral ACs alone. Rivaroxaban was the most frequently used DOAC (79.4%). DOACs were more frequently used in North America/Australia (58.1%), Europe (52.2%), and Asia (47.6%) than in Latin America (29.7%) and the Middle East/South Africa (32.5%). In patients with suspected VTE, most received parenteral AC monotherapy (67.7%). Patients with deep vein thrombosis were more likely to receive DOACs alone than those with pulmonary embolism with or without deep vein thrombosis (36.2% vs 25.9%). Active cancer patients received parenteral AC alone (58.9%), with 25.5% receiving DOAC ± parenteral AC and 12.8% parenteral AC and VKA. A total of 46.5% of pregnant patients received parenteral AC monotherapy, 34.0% were treated with VKA ± parenteral AC, and 19.5% received a DOAC (± parenteral AC). Conclusion: AC treatment patterns vary by patient population, geographic region and site of VTE. Guidelines for AC therapy are not always adhered to.